(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the significance and necessity of creating an initiative environment for youth in the context of New Uzbekistan. It explores the state policy priorities aimed at supporting young people’s intellectual, creative, and professional development. The study highlights how programs such as “Youth are Our Future”, “Youth Notebook”, and “Youth Academy” contribute to enhancing youth activity, entrepreneurship, and innovation. Special attention is given to the social, psychological, and economic importance of encouraging youth initiatives, as well as the role of government and civil society cooperation in unlocking the potential of the younger generation. The article concludes that empowering youth and fostering an environment of creativity and innovation are essential factors for ensuring sustainable national development in New Uzbekistan.